MEASURING THE GROWTH RATE OF DEVELOPMENT IN THE MARKET VALUE OF GLOBAL CRYPTOCURRENCIES AND ITS IMPACT ON TRADING VOLUME - Shaymaa Nihro Jabal Afloogee (Scholars Digest Publishing, 2024)
The study aims to measure the growth rate of development of the market value of global cryptocurrencies and its impact on trading volume and to explain the justifications and origin of cryptocurrencies and trading volume, and the factors affecting them. The currencies "DOGE - Bitcoin - ETH - USDT-" were chosen to be the study sample, extending from the year (2016) to (2022). After delving into the study, I concluded by calculating and analyzing the growth rate of the market value of cryptocurrencies (Ethereum (ETH). (To the presence of various fluctuating contradictions with rises and falls in the currency, as this was indicated in the years of the study sample if the average price of the currency in the year 2016 was at a rate of (577.4225) US dollars, and it decreased over the course of the year 2017 if it reached a rate of (4342.045) US dollars by A little while in the year 2018, the average price of the currency rose at a very significant level to (16,589.42) US dollars. This fluctuation continued in the rise and fall of the currency price over the years (2019-2020-2021) and at a successive rate of (177.7458333-308.7541667-2744.1025) US dollars, and it decreased. The growth rate of the currency's market value in the year 2022 is at a rate of (1922.254167) US dollars. When analyzing the growth rate of the cryptocurrency's market value (Dogecoin (DOGE)), we notice a large fluctuation between the years (2021) and (2022), as very high trading levels were indicated. Unlike previous years, this is an indication of the increase in trading in those years, as the rate of increase reached (0.2076) (0.0970241). Analysis of the growth rate of the market value of cryptocurrencies (Tether (USDT)) indicated significant fluctuation and decline between the years (2021) and (2022), as low levels of trading were indicated at a very low level, unlike previous years, and this is an indication of a decrease in trading in the two years mentioned, amounting to ( 0.917058), (0.916791). When analyzing the trading of the cryptocurrency (Bitcoin), it increased significantly in the year (2021), as very high levels of trading were indicated, unlike the previous and subsequent years, and this is an indication of the increase in trading in that year, as it reached (47,124.99). The study recommends the importance of drawing attention to the information industry and financial technology for global financial markets, especially in developing countries such as Iraq. Since financial technology is the actual means of achieving development, information specialists are being prepared who are trained and prepared to develop stock market financing in the context of contemporary financial technology.
Keywords: cryptocurrencies - types of cryptocurrencies - trading volume.